Development of LKPD Based on Vee Diagram on Diffusion and Osmosis Material in Improving Students' Critical Thinking Skills and Science Process Skills - FATIMATUZZAHRO; Hindriana, Anna Fitri; Ismail, Agus Yadi (Jurnal Report of Biological Education, 2025)
Background: The low levels of students' critical thinking skills and science process skills in diffusion and osmosis material remain a problem in biology learning. This study aims to develop a student worksheet based on the vee diagram to improve students’ critical thinking and science process skills. Methods: The research employed a Research and Development (R&D) approach using the ADDIE model. The subjects were 11th-grade science students at MA Nurul Huda Munjul, consisting of 25 students in the experimental class and 25 in the control class. Instruments included multiple-choice tests, observation sheets, and questionnaires. Data were analyzed using N-gain and t-tests. Results: The developed student worksheet was valid (97.02%) and effectively implemented (90%). Students' critical thinking skills increased with an N-Gain of 0.41 (moderate), compared to 0.05 (low) in the control class. Science process skills also improved to 81.75% (high), outperforming the control class (53.63%). The correlation between critical thinking and science process skills was not significant (r = 0.298 < r table = 0.396; sig. = 0.149). Students’ responses to the student worksheet were in the very good category (85.33%). Conclusion: Thus, the development of vee diagram-based student worksheets on diffusion and osmosis material can enchance student’s critical thinking and science process skills.